1999
DOI: 10.2514/2.3498
|View full text |Cite
|
Sign up to set email alerts
|

Low-Speed Aerodynamics of a Planetary Entry Capsule

Abstract: Results of an investigation of the global aerodynamic coef cients and ow characterization around an Apollostyle capsule model at low speed are presented. Flow features were ascertained quantitatively with laser Doppler velocimetry, digital particle image velocimetry, and hot-wire measurements, as well as qualitatively by ow visualizations. The study revealed a meandering vortex ring around the capsule, well-organized streamwise vortices whose maximum vorticity increased in the recirculating wake before decayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This result is con rmed by the simulations (see Figs. [12][13][14][15]. The results also show that, although the two subsystems are coupled in terms of frequency response, the motion of the parachute is generally limited in amplitude and highly damped.…”
Section: Analysis Of the Resultsmentioning
confidence: 82%
“…This result is con rmed by the simulations (see Figs. [12][13][14][15]. The results also show that, although the two subsystems are coupled in terms of frequency response, the motion of the parachute is generally limited in amplitude and highly damped.…”
Section: Analysis Of the Resultsmentioning
confidence: 82%
“…This time-lag factor is akin to the reduced frequency parameter defined in many studies of dynamic stability [8,17,18], but the value of τ scales this parameter to account for variations in the length scale or the characteristic velocity. The hysteresis of the pitching motion and the subsequent oscillation growth of the vehicle are dependent on the factor τ, and its influence is discussed in following sections.…”
Section: Time Lagmentioning
confidence: 99%
“…2)[4]. Wang et al suggested a similar connection between the oscillation of a body and the motion of the rear stagnation point[8].…”
mentioning
confidence: 95%
“…Wang et al [59]- [61] studied the spectral characteristics of the flow structure at various locations around an Apollo capsule at low speed. Of particular interest were the oscillations of the rear stagnation point because of their possible influence on unsteady loads acting on the aftbody of the vehicle.…”
Section: Strouhal Number (Reduced Frequency Parameter)mentioning
confidence: 99%